2019
DOI: 10.1111/aogs.13789
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamic changes in women with symptoms of supine hypotensive syndrome

Abstract: Introduction: Supine positioning during late pregnancy causes the gravid uterus to compress the inferior vena cava, resulting in dramatic hemodynamic changes. The maintenance of placental perfusion requires maternal circulatory and autonomic adaptations. Women with supine hypotensive syndrome (defined as a drop in systolic blood pressure of anything between 15 and 30 mmHg or an increase in heart rate of 20 bpm, with or without symptoms) may have reduced ability to compensate for the effects of supine positioni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
1
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 22 publications
2
25
1
6
Order By: Relevance
“…The Auckland Stillbirth Study (TASS) 2 was the first to show that women who reported going to sleep supine in the third trimester had a 2.5-fold increased risk of late stillbirth that was independent of other known major risk factors for stillbirth. This finding was biologically plausible and aligned with existing research on the effects of maternal supine position in the third trimester demonstrating vena-caval compression, [3][4][5] decreased maternal cardiac output, 4 6 increased maternal heart rate, 4 5 7 8 decreased uterine perfusion 8 9 Strengths and limitations of this study ► This is the first study to evaluate the success of a nationwide public health campaign on awareness and modification of late pregnancy going-to-sleep position. ► Responses were obtained from a New Zealand-wide convenience sample of pregnant women, with enrichment from socioeconomically disadvantaged communities that have an associated increased risk of stillbirth and health professionals who provide pregnancy care.…”
Section: Introductionsupporting
confidence: 79%
“…The Auckland Stillbirth Study (TASS) 2 was the first to show that women who reported going to sleep supine in the third trimester had a 2.5-fold increased risk of late stillbirth that was independent of other known major risk factors for stillbirth. This finding was biologically plausible and aligned with existing research on the effects of maternal supine position in the third trimester demonstrating vena-caval compression, [3][4][5] decreased maternal cardiac output, 4 6 increased maternal heart rate, 4 5 7 8 decreased uterine perfusion 8 9 Strengths and limitations of this study ► This is the first study to evaluate the success of a nationwide public health campaign on awareness and modification of late pregnancy going-to-sleep position. ► Responses were obtained from a New Zealand-wide convenience sample of pregnant women, with enrichment from socioeconomically disadvantaged communities that have an associated increased risk of stillbirth and health professionals who provide pregnancy care.…”
Section: Introductionsupporting
confidence: 79%
“…Moreover, in recent years, imaging examinations such as ultrasound and MRI have also been used to identify aortocaval compression by a gravid uterus. Humphries et al found that the IVC velocities at the level of origin and at the level of the renal veins was signi cantly reduced, while that of the azygos vein increased signi cantly on MRI [24,25]. This observation was made with the parturient in the supine position compared to the left lateral position in pregnancies between 34-38 weeks' gestation without anesthesia.…”
Section: Discussionmentioning
confidence: 97%
“…Moreover, in recent years, imaging examinations, such as ultrasound and MRI, have been used to identify aortocaval compression by a gravid uterus. Humphries et al found that the IVC velocities at the level of origin and at the level of the renal veins were significantly reduced, while that of the azygos vein increased significantly on MRI [24,25]. This observation was made with the parturient in the supine position, compared with those in the left lateral position, in pregnancies between 34 and 38 weeks of gestation without anesthesia.…”
Section: Discussionmentioning
confidence: 98%